Aproximación al estado del arte de la consultoría y asesoría de las pymes. (2022)
Taking into account the data collected, it was found that, in Colombia, SMEs are forced to liquidate because they have problems, administrative accountants, etc. which causes decisions about these to be made in an unwise way, demonstrating that due to lack of knowledge on some issues, SMEs end up generating financial and legal problems that generate their closures. Consulting and advising SMEs in Pradera and Palmira and perhaps in all of Colombia, would be a great opportunity for SMEs to find a way to stay and continue with their activities, that is why background information was sought to find out some situations in which These methods have given some positive results and also to be certain whether or not advisory services and consultancies have been developed in SMEs.